La matrice de la race: généalogie sexuelle et coloniale de la nation française - Dorlin, Elsa (La Découverte poche, 2009)
La race a une histoire, qui renvoie à l'histoire de la différence sexuelle. Au XVIIIe siècle, les discours médicaux affligent le corps des femmes de mille maux : « suffocation de la matrice » « hystérie », « fureur utérine », etc. La conception du corps des femmes comme un corps malade justifie efficacement l'inégalité des sexes. Le sain et le malsain fonctionnent comme des catégories de pouvoir. Aux Amériques, les premiers naturalistes prennent alors modèle sur la différence sexuelle pour élaborer le concept de « race » : les Indiens Caraïbes ou les esclaves déportés seraient des populations au tempérament pathogène, efféminé et faible. Ce sont ces articulations entre le genre, la sexualité et la race, et son rôle central dans la formation de la Nation française moderne qu'analyse Elsa Dorlin, au croisement de la philosophie politique, de l'histoire de la médecine et des études sur le genre. L'auteure montre comment on est passé de la définition d'un « tempérament de sexe » à celle d'un « tempérament de race ». La Nation prend littéralement corps dans le modèle féminin de la « mère », blanche, saine et maternelle, opposée aux figures d'une féminité « dégénérée » ? la sorcière, la vaporeuse, la vivandière hommasse, la nymphomane, la tribade et l'esclave africaine. Il apparaît ainsi que le sexe et la race participent d'une même matrice au moment où la Nation française s'engage dans l'esclavage et la colonisation.
Keywords: 1700-1799; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; premier cycle; périodes historiques; représentation; représentation des femme*; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; sud global; système colonial; systèmes d'oppressions; thématiques; violences

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

Policing the national body: Sex, race, and criminalization - Silliman, Jael Miriam; Bhattacharjee, Anannya; Davis, Angela Y.; Committee on Women, Population, and the Environment (South End Press, 2002)
Keywords: amériques; approches et analyses; corps; environnement; justice reproductive; maternité; nationalisme; racisme; régions géographiques; santé; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences